An integrated methodology for chemical product design: application to cosmetic emulsions (2018)
Abstract The design of optimal mixtures is a major challenge in many industrial sectors, especially for formulated products such as cosmetics. Due to the large number of different combinations of ingredients and their quantities, a critical issue is how to define a narrow search space using available knowledge. For this purpose, besides considering some key physicochemical properties of the final product, it is of paramount importance to take into account the performance of the product as perceived by the final consumer. Here, we have proposed a methodology to find a set of plausible formulations for emulsified cosmetic products, based on a fuzzy integral analysis of the consumer preferences and integrated into a mixed-integer optimization tool that incorporates available heuristic rules and property models. Two case studies of cosmetic emulsions were given to illustrate the methodology. In a first example using hair conditioners, the rheological, textural, and microstructural properties of nine alternative formulations manufactured at a lab scale were measured to validate the modelling of emulsified products. Then, two commercial samples of skin moisturizers were tested to identify the most relevant consumer attributes using fuzzy measures. Based on this assessment, ten computer-generated solutions with minimum ingredient costs were also manufactured and evaluated, showing that the proposed methodology could be well adapted to accelerate reformulation or benchmarking processes. Using this approach, product designers could also estimate the relevance and interactions of subjective consumer attributes and guide the design of other formulated products.